2016
DOI: 10.1007/s11071-016-3230-2
|View full text |Cite
|
Sign up to set email alerts
|

Modal characteristics of a rotating flexible beam with a concentrated mass based on the absolute nodal coordinate formulation

Abstract: A new dynamic model of a rotating flexible beam with a concentrated mass located in arbitrary position is derived based on the absolute nodal coordinate formulation, and its modal characteristics are investigated in this paper. To consider the concentrated mass at an arbitrary location of the beam, a Dirac's delta function is used to express the mass per unit length of the beam. Based on the proposed dynamic model, the frequency analysis is performed. The nonlinear equation is transformed into the linear one v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
2
22
2
Order By: Relevance
“…The effect of rotation speed on the nonlinear vibrations of the beam and particularly on the hardening/softening behavior of its resonances and the occurrence of high amplitude jump phenomena were investigated. A new dynamic model of a rotating flexible beam with a condensed mass positioned in an arbitrary location, based on the absolute nodal coordinate formulation, was investigated by Zhang et al [2]. They found that both the magnitude and the direction of the condensed mass impact the normal frequencies and the mode shapes.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of rotation speed on the nonlinear vibrations of the beam and particularly on the hardening/softening behavior of its resonances and the occurrence of high amplitude jump phenomena were investigated. A new dynamic model of a rotating flexible beam with a condensed mass positioned in an arbitrary location, based on the absolute nodal coordinate formulation, was investigated by Zhang et al [2]. They found that both the magnitude and the direction of the condensed mass impact the normal frequencies and the mode shapes.…”
Section: Introductionmentioning
confidence: 99%
“…Saad et al 11 presented the mathematical model of an Euler-Bernoulli link using the Lagrange equations by taking into account the foreshortening effect and incorporating a payload having mass, inertia, and offset. Zhang et al 12 studied the natural frequencies of a flexible Euler-Bernoulli rotating beam with a concentrated mass at an arbitrary position. The effect of variation of the mass, rotating frequency, and mass position on the natural frequencies has been discussed thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al. 12 studied the natural frequencies of a flexible Euler–Bernoulli rotating beam with a concentrated mass at an arbitrary position. The effect of variation of the mass, rotating frequency, and mass position on the natural frequencies has been discussed thoroughly.…”
Section: Introductionmentioning
confidence: 99%
“…Rotating structures have seen a great variety of applications to industrial products, such as a turbo engine, a helicopter and a spinning solar sail [1][2][3][4]. Previous studies have shown that the dynamic characteristics of a rotating structure are more complicated than non-rotating ones because of the centrifugal stiffening effect [1,3,[5][6][7]. For example, the eigenfrequency loci veering, eigenfrequency loci crossing and mode switching phenomena have been observed with an increase of the rotating speed.…”
Section: Introductionmentioning
confidence: 99%